2013
DOI: 10.4314/jmbs.v2i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Positive malignant margins in clinically diagnosed and excised be-nign breast lumps: a five year retrospective study at the Korle-Bu teaching hospital, Ghana

Abstract: This study was aimed at utilizing retrospective descriptive data to evaluate the percentage of clinically benign breast lumps that turned out to be histologically malignant and the prevalence of positive tumour margins among the malignant cases. A total of 2,917 registered cases of excised breast lump at the Department of Pathology spanning January 2005 to December 2009 were reviewed to evaluate the presence of malignancy and positive margins. Three hundred and twenty-two (11.0%) of the excised breast lumps we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 19 publications
(25 reference statements)
3
7
0
Order By: Relevance
“…In our study, the mean age of women with positive margins was 53.4 years, with a modal age group of 40-49 years. This age group is similar to the findings in previous studies in Ghana [9,8,11]. Young age has generally been found to be associated with an increased risk of local recurrence after breast conserving surgery [21,32,35].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our study, the mean age of women with positive margins was 53.4 years, with a modal age group of 40-49 years. This age group is similar to the findings in previous studies in Ghana [9,8,11]. Young age has generally been found to be associated with an increased risk of local recurrence after breast conserving surgery [21,32,35].…”
Section: Discussionsupporting
confidence: 90%
“…Our rate of 21.1% is in accord with these studies. However, this value is lower than Der et al studies of positive malignant margins in clinically diagnosed and excised benign breast lumps, in which they found that 322 (11.0%) out of 2,917 clinically benign lumps during the study period were malignant and that 142 (44.1%) had positive margins [9]. The high rate of positive margin in that study was because the excisions were not wide local excisions.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The greatest male and female cases were having sub-clinical hyperthyroidism and they were in older age groups in the present study. The prevalence of thyroid disorders has been found to increase linearly with age and virtually all thyroid diseases are common in women (Der et al, 2013). Other researchers showed that in females, thyroid disorders were most common as compared to males (Bustany, 2011, GovindanKutty et al, 2013, Al-Msari et al, 2014, Shahrani et al, 2016 and thyroid disorders would be increased with the advancing age (Mariotti et al, 1995).…”
Section: Discussionmentioning
confidence: 97%